Evaluation of some Achillea L. accessions based on morphological, cytological and chemical characteristics - Inotai, K.; Németh, É.; Pintér, I.; Jager, K.; Sárosi, Sz. (International Journal of Horticultural Science, 2008)
Taxonomical evaluation of six taxa of the Achillea aggregate was carried out to determine their potential for breeding and cultivation. We used complex morphological, cytological and chemical aspects of characterisation. Three taxa of tetraploid genom and high chamazulene contents (33-40% ess.oil) proved to be A. collina Becker. A strain of wild origin had also high -bisabolol content and high oil level, comparable with the selected cultivars. A population was identified as new chemotype of A. pannonica Scheele with typical morphological and cytological traits, a wide sesquiterpene spectrum but lacking of 1.8 cineole and -pinene. We found a mixed population which consisted of both A. collina and A. pannonica plants. A tetraploid, azuleneless taxon could be concluded as A. pratensis Saukel and Langer not described before in Hungary. The diverse performance of the populations calls the attention to the significance of controlled plant raw in phytopharmaceutical products.